Estudo das imperfeições locais e globais no cálculo da resistência de elementos de estruturas de aço - Boeira, Diego Juliano da Rosa (2017)
Evaluation of the strength capacity of steel sections requires the correct analysis of the structure's forces and must comply with the limit states proposed by the current standards -especially here, NBR 8800 (ABNT 2008). Problems and mistakes in erection of structures, or due to fabrication process of profiles manufacturing, lead to the appearance of several imperfections. These imperfections, local and global, can cause several eccentricities and changes in the distribution of forces, causing the structural elements to flexural compressionand, consequently, out of the tolerance limits proposed by the cited Brazilian standard, this, for right, can lead to errors in the calculation of the section resistant capacity. Even if finite elements software allows advanced analysis using the elastic buckling modes, leading to more accurate results, there are still doubts in the operation of such systems and structural designs, even, by experienced engineers who do not understand the behavior of the structure with its deformed geometry. Thus, the aim of the present study was to analyze the effect of local, global and integrated geometric imperfections on modeled structures with geometric nonlinear analysis, varying the imperfections and including it through elastic buckling modes. This evaluation was done in isolated bars and 2D and 3D frames composed of rolled sections, through the structural analysis methods proposed by NBR8800, comparing, later, with the method proposed in the last revision of ANSI/AISC 360 (2016), which uses advanced analysis of structures and considers local and global imperfections modeled by directly way. In this way, it is inferred as main results of this research that the imperfections influence in a significant way the forces and conditions of structure stability. The method proposed by the ANSI/AISC 360 (2016) demands a more careful evaluation of the structural analysis, requiring of the calculating engineer greater knowledge for application of the method that, under ideal conditions, can lead to reductions in material use.